Specific Aspects of Teaching Geographical and Origin Names to Foreign Language Students of the Faculty of Medicine - Svanidze, Daphine (Modern Issues of Medicine and Management, 2025)
This paper explores the specific features and instructional process of teaching geographical and origin-related nouns to foreign students of the Faculty of Medicine at Geomedi University. The students are learning Georgian as a second language. These types of lexical units play an essential role both linguistically and in everyday communication, as they express the connection between people or objects and geographical spaces. For foreign learners, acquiring and understanding such nouns presents challenges due to the complexity of word formation processes, the diversity of affixes, and the nuances of meaning. The study analyzes the structural characteristics of geographical and origin-related nouns, identifies typical learner errors, and investigates their underlying causes. Special attention is given to effective teaching strategies, including the use of visual materials, dialogic texts, and intercultural activities. These approaches significantly contribute to the development of students’ linguistic competence and the enhancement of their cultural awareness. The proposed methods facilitate a clearer understanding of how spatial relationships are expressed in Georgian and promote their functional use in communication.